Plague, Martyrdom, and Quarantine: Classical Hadith Exegesis and Contemporary Pandemic Governance - Deasy Silvya Sari; Nursiswati; Anwar Radiamoda; Dadah (Sinergi International Journal of Islamic Studies, 2026)
The COVID-19 pandemic renewed scholarly interest in Prophetic traditions concerning plague (ṭāʿūn) and their ethical relevance to contemporary public-health crises. While previous studies have primarily examined plague-related hadiths from theological and juridical perspectives, limited attention has been given to their potential contribution to contemporary discussions on global health governance and Islamic bioethics. This study aims to reconstruct an ethical framework derived from plague-related hadiths and to examine its relevance to contemporary pandemic governance. The study analyzes nine selected hadiths drawn from Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, Sunan al-Nasāʾī, Sunan Ibn Mājah, al-Muwaṭṭaʾ of Mālik, and Musnad Aḥmad using a thematic (mawḍūʿī) approach that combines takhrīj, sanad and matn criticism, thematic classification, and contextual interpretation. The narrations were selected based on their relevance to plague, martyrdom, quarantine, disease prevention, and communal responsibility and were limited to reports classified as ṣaḥīḥ or ḥasan. The findings identify three interconnected ethical themes: plague as a divine trial and martyrdom, quarantine and preventive responsibility, and spiritual resilience in times of crisis. These themes suggest important conceptual convergences with contemporary principles of pandemic governance, including solidarity, proportionality, reciprocity, equity, and the protection of vulnerable populations. Rather than evaluating policy effectiveness, this study offers a conceptual reconstruction of Prophetic plague ethics and argues that these traditions continue to provide relevant ethical resources for contemporary discussions on pandemic governance, Islamic bioethics, and public-health ethics.